PELAKSANAAN KOMUNIKASI TERAPEUTIK OLEH PERAWAT TERHADAP PASIEN RAWAT INAP DI BADAN LAYANAN UMUM DAERAH (BLUD) RS SEKARWANGI KABUPATEN SUKABUMI - Rhodiyat Fajar Salim; Tuah Nur (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
Therapeutic communication is a communication made by nurses as professionals that aims to help the healing process of patients. Reality is happening in BLUDs RS Sekarwangi Sukabumi, health care service users, including patients who are hospitalized there who complain of discomfort due to communication. This problem is amplified when confirmed to the public relations department of the hospital BLUDs Sekarwangi, which states that: